PENYEDIAAN LAYANAN JASA DESAIN GAMBAR KERJA SEBAGAI IMPLEMENTASI KESIAPAN BERWIRAUSAHA SISWA SMK 2 SURABAYA JURUSAN DPIB - Moh Faisal Faris; Widjaja, Andang; Supriyanto, Yunaidi (Universitas Islam Balitar Blitar, 2024)
Developing entrepreneurial interest in vocational school students is an effort. Vocational school students are prepared to work in the industrial world. Vocational school graduates are also encouraged to become creative entrepreneurs. Students majoring in Modeling Design and Building Information, armed with the competencies they have acquired during the learning process at school, can create their own businesses. Students can play a role in running their business in the field of design as planners independently. One form of business that can be developed is a business in the field of working drawing design services. The implementation method in the design services business consists of the stages of entrepreneurship, design services, planning working drawings, including preparation stages, market research and product formulation, and marketing strategies. Every business cannot be separated from analyzing a SWOT analysis, namely finding crucial aspects of the strengths, weaknesses, opportunities and threats experienced by a company. These four aspects are useful for increasing strengths, reducing weaknesses, building better opportunities, and avoiding threats. After carrying out a simple analysis of all aspects in accordance with SWOT, a business strategy can be taken based on the aim of optimizing opportunities from the strength aspect. The business strategy that can be implemented is to optimize opportunities through existing strengths. The strength of the design services business lies in the competency of each SMKN 2 Surabaya student as a business actor. Opportunities in the technology era must be maximized in achieving publication, promotion and dissemination of information related to the business sector. The advantage of this service business model is that it can channel interest in design into activities that generate financial profits. Business thinking must be instilled in students as potential entrepreneurs